2020
DOI: 10.1002/jbm.b.34661
|View full text |Cite
|
Sign up to set email alerts
|

Development of novel surface coating composed of MDPB and MPC with dual functionality of antibacterial activity and protein repellency

Abstract: Resin-based reconstructive/restorative materials with antibacterial effects are potentially useful for preventing dental and oral diseases. To this end, the immobilization of an antibacterial component on the surface of a resin by incorporating polymerizable bactericide such as a quaternary ammonium compound-monomer 12-methacryloyloxydodecylpyridinium bromide (MDPB) is an effective technique. However, the effectiveness of immobilized bactericide is reduced by salivary protein coverage. We address this issue by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(45 citation statements)
references
References 28 publications
(42 reference statements)
0
41
0
Order By: Relevance
“…They suggested that an MPC polymer coating in the oral cavity may suppress oral bacterial adherence [ 95 ]. Recent research has focused on the combined application of MPC and other antimicrobial agents, such as DMAHDM [ 96 ], S-PRG [ 97 ] and MDPB [ 22 ]. The relevant content will be explained in detail in the multi-functional strategy module below.…”
Section: Current Antimicrobial Strategies Of Resin Compositesmentioning
confidence: 99%
“…They suggested that an MPC polymer coating in the oral cavity may suppress oral bacterial adherence [ 95 ]. Recent research has focused on the combined application of MPC and other antimicrobial agents, such as DMAHDM [ 96 ], S-PRG [ 97 ] and MDPB [ 22 ]. The relevant content will be explained in detail in the multi-functional strategy module below.…”
Section: Current Antimicrobial Strategies Of Resin Compositesmentioning
confidence: 99%
“…We believe PEP-PC can be used in dental applications. Thongthai et al [ 71 ] synthesized MPC polymers with 12-methacryloyloxydodecylpyridinium bromide (MDPB) and BMA and coated them on the surface of a resin for controlling bacterial growth in the oral environment ( Figure 5(a,b) ). This coating provided a more hydrophilic surface than that coated by MDPB and reduced the adsorption of BSA and salivary protein.…”
Section: Antibiofouling and Antimicrobial Propertiesmentioning
confidence: 99%
“…Scale bars = 30 μm. Reprinted with permission from [ 71 ]. Copyright (2020) Wiley.…”
Section: Antibiofouling and Antimicrobial Propertiesmentioning
confidence: 99%
“…It was found that the incorporation of DHMAI in resin can improve antimicrobial effectiveness, while the addition of MPC to DHMAI did not provide a better antimicrobial effectiveness and affected the mechanical properties of composites. Thongthai et al [ 73 ] utilized the MPC polymer possessing the function of protein repellency to address the problem, in which the effectiveness of immobilized bactericide was reduced by salivary protein coverage. Both the MDPB and MPC were able to fabricate a novel copolymer, which served as a surface coating on a methacrylate-based dental resin, but the MDPB/MPC copolymer exhibited a more hydrophilic surface than that provided by MDPB, reducing the adsorption of salivary protein.…”
Section: Antimicrobial Propertiesmentioning
confidence: 99%